(untitled) (Web of Teachers: Inderscience Research, 2024)
The article provides information about Usman Nasir, a son of Namangan, a fiery soul, and his sad fate. The rebellious spirit in the poet’s unanswered letters, immortal works and poems, which are not known to the people, are explained with examples. According to the poet, what is the main duty of a person is analyzed.